Stability studies of binding and functional anti-vaccine antibodies. (May 2014) - Hendriks, Jenny; Stals, Coby; Versteilen, Amanda; Mommaas, Bregje; Verhoeven, Mariëlle; Tirion, Felicia; Haak, Mariska ter; Ribbens, Wolf; Bosch, Marije; Trommel, Martijn; Kostense, Stefan
Background: As most vaccines exert their protective capacity by eliciting pathogen-specific antibodies, antibody assays assessing immunogenicity of vaccines in development should be well characterized. Part of the validation of immunogenicity assays for vaccines is the study of stability of antibodies in serum.Materials & methods: Stability of antibodies in human serum was assessed by circumsporozoite-binding IgG ELISA designed for assessing the immunogenicity of a malaria vaccine under development, adenovirus neutralization assay, designed to assess neutralizing antibodies against adenovirus and commercially available test kits for hepatitis A and B.Results: Stability studies indicated stability of serum-binding IgG antibodies and serum-neutralizing antibodies in: long-term storage below -65°C and -20°C; short-term storage; multiple freeze/thaw rounds; during shipment; and during heat inactivation.Conclusion: Results have shown the stability of both binding and functional polyclonal antibodies in human serum under stable storage and common usage circumstances.